Pengembangan E-Modul Fisika Berbasis Masalah dengan Pendekatan Flipped Classroom Menggunakan Software Sigil Sebagai Alternatif Media Pembelajaran di Masa Pandemic Covid-19 - Asep Dwi Purwoto; Suharno Suharno; Sukarmin Sukarmin (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to develop a problem-based physics e-module with a flipped-classroom approach using sigil software that is fit for use as an alternative media of learning physics simple harmonic motion material for students of class XI MIPA SMA Muhammadiyah 2 Bandar Lampung during the COVID-19 pandemic. The type of research used is research and development, with an ADDIE development model consisting of analysis, design, development, implementation, and evaluation. The data collection instruments used were interview guide sheets, observation guide sheets, and questionnaire sheets. The research data obtained were then analyzed descriptively qualitatively. Based on the results of the feasibility assessment and data analysis carried out, it was concluded that the problem-based e-module using Sigil software with a flipped-classroom approach was feasible to use